2016
DOI: 10.1158/2159-8290.cd-15-1032
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ and CCL2 Cooperate to Redirect Tumor-Infiltrating Monocytes to Degrade Fibrosis and Enhance Chemotherapy Efficacy in Pancreatic Carcinoma

Abstract: Dense fibrosis and a robust macrophage infiltrate are key therapeutic barriers in pancreatic ductal adenocarcinoma (PDAC). CD40 activation can circumvent these barriers by inducing macrophages, originating from peripheral blood monocytes, to deplete fibrosis. The precise mechanism and therapeutic implications of this anti-fibrotic activity, though, remain unclear. Here, we report that IFN-γ and CCL2 released systemically in response to a CD40 agonist cooperate to redirect a subset of Ly6C+CCR2+ monocytes/macro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
229
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(241 citation statements)
references
References 52 publications
(95 reference statements)
10
229
1
1
Order By: Relevance
“…In comparison, KPC mice treated with vehicle control, or with the combination of Gem/nP, had no regressions or stabilization of disease, and only 1/14 mice treated with αCD40 alone had stable disease at the 14-day time point after the start of therapy (Figure 4A). The previously reported 30% rate of regressions to αCD40 observed in tumor-bearing KPC mice (Beatty et al, 2011) was not observed here using KPC mice that are fully C57BL/6 backcrossed, although a recent report confirms the macrophage-dependency of αCD40 monotherapy in this strain of mice (Long et al, 2016). Moreover, in contrast to the previously reported macrophage-dependent (T cell-independent) regressions in KPC mice treated with CD40 alone (Beatty et al, 2011), here the response rate was completely lost if mice treated with Gem/nP/αCD40 were first depleted of CD8 + T cells (Figure 4A), indicating a shift to a T cell-dependent immune response against spontaneous PDA when combining both Gem and nP with αCD40.…”
Section: Resultscontrasting
confidence: 78%
“…In comparison, KPC mice treated with vehicle control, or with the combination of Gem/nP, had no regressions or stabilization of disease, and only 1/14 mice treated with αCD40 alone had stable disease at the 14-day time point after the start of therapy (Figure 4A). The previously reported 30% rate of regressions to αCD40 observed in tumor-bearing KPC mice (Beatty et al, 2011) was not observed here using KPC mice that are fully C57BL/6 backcrossed, although a recent report confirms the macrophage-dependency of αCD40 monotherapy in this strain of mice (Long et al, 2016). Moreover, in contrast to the previously reported macrophage-dependent (T cell-independent) regressions in KPC mice treated with CD40 alone (Beatty et al, 2011), here the response rate was completely lost if mice treated with Gem/nP/αCD40 were first depleted of CD8 + T cells (Figure 4A), indicating a shift to a T cell-dependent immune response against spontaneous PDA when combining both Gem and nP with αCD40.…”
Section: Resultscontrasting
confidence: 78%
“…CCL2-mediated recruitment of MDSCs, monocytes, and macrophages supports colorectal carcinogenesis, endometrial cancer growth, and breast cancer metastasis (2729). However, anti-CD40 agonist treatment induces CCL2-recruited monocytes degrade fibrosis in an IFNγ-dependent manner, improving gemcitabine efficacy in pancreatic carcinoma (30). CCL2 can also recruit functional antigen-presenting cells in the context of chemotherapy, in which immunogenic cell death is likely to be of major importance (31).…”
Section: Discussionmentioning
confidence: 99%
“…Immuohistochemistry on frozen tissue sections or formalin-fixed paraffin embedded tissues was performed as previously described [17]. Immunohistochemical staining of paraffin tissues was performed using the Ventana Discovery Ultra automated staining system.…”
Section: Methodsmentioning
confidence: 99%